IMPLEMENTASI MANAJEMEN KESISWAAN DI MA AL-FALAH GUNUNG KASIH KECAMATAN PUGUNG KABUPATEN TANGGAMUS: INDONESIA - Muhammad Fajri RS; Muhtarom (JOURNAL MANAJEMEN PENDIDIKAN ISLAM AL IDARAH, 2017)
AbstractThis study aims to find out the process of implementation of new admissions, implementation of learningprogress data, guidance and supervision of student discipline and monitoring in Madrasah Aliyah Al-FalahGunung Kasih.This research is a qualitative research. The methods used are observation, interview and documentation.Data analysis phase is data reduction, data display and conclusion and verification (Conclusion andverification).Implementation of student management at Madrasah Aliya AL Falah Gunung Kasih already follow theconcepts of student management, this can be seen directly in the implementation of new student acceptance,data collection of student learning progress, guidance and coaching student discipline and monitoring has beenapplied by component of madrasa. There are factors hindering the implementation of student management,among others: (a) Student management is not maximal, human resources, especially administrative staff ofstudent management, (b) no clear command from the head of madrasah (c) Less absorbing and listening tocommunity reports) Monitoring is only done by the principal assisted by headmaster and guidance teachercounseling while the community is not involved.AbstrakPenelitian ini bertujuan untuk mengetahui proses pelaksanaan penerimaan siswa baru, pelaksanaanPendataan kemajuan belajar, pengelolaan bimbingan dan pembinaan disiplin siswa serta pelaksanaan monitoringdi Madrasah Aliyah Al-Falah Gunung Kasih.Penelitian ini adalah penelitian kualitatif. Metode yang digunakan observasi, wawancara dandokumentasi. Tahap analisis datanya adalah reduksi data, display data serta penarikan kesimpulan dan verifikasi(Conclusion and verification).Pelaksanaan manajemen kesiswaan di Madrasah Aliya AL Falah Gunung Kasih sudah mengikuti konsepkonsep manajemen kesiswaan, hal ini bisa dilihat langsung dalam pelaksanaan dari penerimaan siswa baru,pendataan kemajuan belajar siswa, bimbingan dan pembinaan disiplin siswa serta monitoring sudah diterapkanoleh komponen madrasah. Terdapat faktor penghambat pelaksanaan manajemen kesiswaan antara lain : (a)Pengelolaan kesiswaan kurang maksimal, sumber daya manusia khususnya tenaga administrasi pelaksanamanajemen kesiswaan, (b) tidak ada komando yang jelas dari kepala madrasah (c) Kurang menyerap danmendengarkan laporan masyarakat, (d) Monitoring hanya dilakukan oleh kepala sekolah dibantu wakil kepaladan guru BK sedangkan masyarakat tidak dilibatkan.Kata kunci : Manajemen, Kesiswaan